ISOLATION AND CHARACTERIZATION OF PHOSPHOLIPASE A2 FROM THE SPINES VENOM OF THE CROWN-OF-THORNS STARFISH ISOLATED FROM PAPUA ISLAND - IMELDA KRISANTA ENDA SAVITRI; MUHAMADSAHLAN; FERA IBRAHIM; ANONDHO WIJANARKO (International Journal of Pharma and Bio Sciences, 2012)
The crown of thorns starfish (COT) Acanthaster planci spine venom contains phospholipase A2 (PLA2). Recently, we have reported the rapid and efficient purification methods of it, especially for the PLA2 from COT spine isolated in Ambon islands. The COT isolated in Papua islands has a different morphology compared with COT in Ambon islands, the spines were bigger and longer. To confirm the availability of PLA2 in COT isolated in Papua, we isolated it by using our method. The activity of crude PLA2 of it higher compare with crude PLA2 isolated from COT spines from Ambon islands. Unfortunately, fractionated of ammonium sulfate at a concentration 20% is only slightly increased three times compared with the crude PLA2. The result shows that the PLA2 is calcium-dependent enzyme.